Optical fiber telecommunications VI. - Kaminow, Ivan P., 1930-; Li, Tingye; Willner, Alan E. (Academic Press, 2013)
Optical Fiber Telecommunications VI (A & B) is the sixth in a series that has chronicled the progress in the R & D of lightwave communications since the early 1970s. Written by active authorities from academia and industry, this edition brings a fresh look to many essential topics, including devices, subsystems, systems and networks. A central theme is the enabling of high-bandwidth communications in a cost-effective manner for the development of customer applications. These volumes are an ideal reference for R & D engineers and managers, optical systems implementers, university researchers and students, network operators, and investors. Volume A is devoted to components and subsystems, including photonic integrated circuits, multicore and few-mode fibers, photonic crystals, silicon photonics, signal processing, and optical interconnections.